Cardio-thoracic surgical patients' experience on bedside nursing handovers: Findings from a qualitative study. (August 2016) - Lupieri, Giulia; Creatti, Chiara; Palese, Alvisa
Summary: The purpose of this study was to describe the experiences of postoperative cardio-thoracic surgical patients experiencing nursing bedside handover. A descriptive qualitative approach was undertaken. A purposeful sampling technique was adopted, including 14 patients who went through cardio-thoracic surgery and witnessed at least two bedside handovers. The study was performed in a Cardio-thoracic ICU localised in a Joint Commission International accredited Academic Hospital in north-eastern Italy from August to November 2014. The experience of patients participating at the bedside handover is based on four main themes: (1) 'discovering a new nursing identity', (2) 'being apparently engaged in a bedside handover', (3) 'experiencing the paradox of confidentiality' and (4) 'having the situation under control'. With the handover performed at the bedside in a postoperative setting, two interconnected potential effects may be achieved with regard to patients, nurses and the nursing profession. Nurses have a great opportunity to express their closeness to patients and to promote awareness of the important growth that nursing has achieved over the years as a profession and discipline. Therefore, patients may better perceive nursing competence and feel safer during the postoperative care pathway. They can appreciate nurses' humanity in caring and trust their competence and professionalism.